The Role Of Mutual Legal Assistance In Returning Assets Results Of Corruption - Frento T. Suharto (UNISSULA Semarang, 2022)
One of the unresolved legal issues in Indonesia is corruption. The problem is that law enforcement is not optimal until assets resulting from criminal acts of corruption which are often beyond the borders of the country, making it difficult to return them are often a separate problem. The implementation of Mutual Legal Assistance (MLA), abbreviated as MLA, which is expected to help law enforcers, is not yet optimal. As a member country of the United Nations Convention Against Corruption (UNCAC), Indonesia does not yet have a regulatory framework that comprehensively regulates the aspects recommended by the convention. This study aims to find out about the efforts and mechanisms for optimizing the role of MLA in returning assets resulting from corruption in Indonesia, especially those located abroad. This article is the result of a normative juridical research conducted by means of a literature study and interviews with related sources, using a statutory and comparative approach. This article concludes that to optimize the role of MLA, several steps are needed, such as implementing MLA in a more detailed technical format, optimizing the role of law enforcement as its implementer, and adopting the concept of Non-Conviction Based Asset Forfeiture (NCB) as the substance of MLA.